New perspectives on regional and interregional obsidian circulation in prehistoric and early historic Arabia - Khalidi, Lamya; Lewis, Krista; Gratuze, Bernard (Proceedings of the Seminar for Arabian Studies, 2012)
Until recently, the western Arabian Peninsula has had an enigmatic role in the large-scale prehistoric exchange networks of the greater ancient Near East. New geological and archaeological data recovered from obsidian-rich zones as well as sites in southwest Arabia and beyond, have begun to elucidate the region’s unprecedented position as a regional and interregional supplier and consumer of obsidian as early as the sixth millennium BC. This paper reviews recent data on obsidian sourcing in Arabia as well as new source matches to archaeological sites in the major source zone supplying obsidian across the region, namely the Dhamār highland plains of Yemen, and discusses the results within the context of previous obsidian research. These data offer new perspectives that will allow us to broaden our understanding of the development of ancient Near Eastern societies over time, to include south-west Arabia. Furthermore, these new data provide us with a preliminary diachronic view of the intensification and fluctuations in obsidian circulation and their relationship to the major societal transformations that occurred between the Neolithic and early historic periods in the region.